The effect of augmented feedback on the performance and learning of gross motor and sport-specific skills: A systematic review. (November 2022) - Petancevski, Emma Louise; Inns, Joshua; Fransen, Job; Impellizzeri, Franco Milko
Abstract: Background: Augmented feedback is often provided by coaches and practitioners as a method to enhance the performance of athletes and learners. When implementing a feedback intervention, it is important to assess the expertise of the learner and the complexity of the skill, to ensure an appropriate feedback modality, frequency, and timing is provided. However, researchers have a limited understanding of how these variables interact to influence the performance and learning of gross motor and sport-specific skills. Objectives: The purpose of this systematic review was to examine the effects of augmented feedback on the performance and learning of gross motor and sport-specific skills in an adult population. Methods: A systematic literature search was conducted on electronic databases, PubMed, Web of Science and PsycINFO, from inception to March 2020, with a revised search completed to January 2022. The search terms used were related to augmented feedback and motor performance and learning. Studies were included if they consisted of a randomised control trial with pre- and retention-testing measures, which investigated an AF intervention on a gross motor and/or sport-specific skill in a healthy adult population. Risk of bias was assessed using the revised Cochrane risk-of-bias tool for randomised trials (RoB2). Results: Twenty-four studies were included, with a total of 895 participants. Most studies reported a learning improvement following the provision of AF. One study documented a decrease in performance, and two studies reported no learning improvement Conflicting evidence was reported regarding which feedback frequency, timing, and duration was most appropriate. Furthermore, the inconsistency in methodological designs (control group types; timing of retention-tests; lack of retention tests) limited the comparisons that could be made between studies. Eighteen studies reported a high risk of bias, with the remaining six presenting some concerns. Conclusion: Although studies have shown positive effects of AF on the performance and learning of gross motor and sport-specific skills, the majority are at a high risk of bias. Additionally, studies lacked standardisation in methodology, and results surrounding features of AF interventions were conflicting. Despite the conceptually sound rationale, further research is required to provide stronger evidence and a more robust understanding to better inform practitioners on how AF truly impacts the performance and learning of gross motor and sport-specific skills. Registration: This systematic review was registered on the Open Science Framework (https://osf.io/mrxzg ) (10.17605/OSF.IO/MRXZG) Highlights: Augmented feedback is likely to improve the performance and learning of gross motor and/or sport-specific skills. Lack of negative/null findings limits our understanding of how augmented feedback interventions influence learning. The optimal feedback frequency, timing and duration remains unclear. Greater standardization and consistency in the methodology and more rigorous methodological reporting is required.